2021
DOI: 10.48550/arxiv.2111.14074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rate-Splitting Multiple Access for Satellite-Terrestrial Integrated Networks:Benefits of Coordination and Cooperation

Abstract: This work studies the joint beamforming design problem of achieving max-min rate fairness in a satellite-terrestrial integrated network (STIN) where the satellite provides wide coverage to multibeam multicast satellite users (SUs), and the terrestrial base station (BS) serves multiple cellular users (CUs) in a densely populated area. Both the satellite and BS operate in the same frequency band. Since rate-splitting multiple access (RSMA) has recently emerged as a promising strategy for non-orthogonal transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…To further guarantee seamless and ubiquitous service, integrated terrestrial-satellite networks have been proposed and are a promising approach. RSMA has been studied in [131], [193], [195] for integrated terrestrial-satellite networks, where RSMA is shown to achieve significant sum-rate, secrecy rate, and EE gains over conventional MU-LP.…”
Section: ) Simultaneous Wireless Information and Power Transfer (Swipt)mentioning
confidence: 99%
“…To further guarantee seamless and ubiquitous service, integrated terrestrial-satellite networks have been proposed and are a promising approach. RSMA has been studied in [131], [193], [195] for integrated terrestrial-satellite networks, where RSMA is shown to achieve significant sum-rate, secrecy rate, and EE gains over conventional MU-LP.…”
Section: ) Simultaneous Wireless Information and Power Transfer (Swipt)mentioning
confidence: 99%
“…Compared with satellites and terrestrial BSs, UAVs enjoy much higher mobility, ease of deployment, and may act as aerial ISAC platforms, relays or sensing targets, which present great compatibility with the SAGIN to enhance ISAC services [1]. Note that RSMA has been demonstrated to be very promising for satelliteterrestrial/aerial integrated networks [21], [22] and satellite ISAC systems [9] due to its powerful interference management capability. Hence, the interplay between RSMA-assisted ISAC and SAGIN is worth being investigated.…”
Section: B Rsma-assisted Isac With Saginmentioning
confidence: 99%